Striatal Transplantation of Human Dopaminergic Neurons Differentiated from Induced Pluripotent Stem Cells Derived from Umbilical Cord Blood Using Lentiviral Reprogramming. Issue 10 (October 2015) - Effenberg, Anna; Stanslowsky, Nancy; Klein, Alexander; Wesemann, Maike; Haase, Alexandra; Martin, Ulrich; Dengler, Reinhard; Grothe, Claudia; Ratzka, Andreas; Wegner, Florian
Human induced pluripotent stem cells (hiPSCs) are promising sources for regenerative therapies like the replacement of dopaminergic neurons in Parkinson's disease. They offer an unlimited cell source that can be standardized and optimized to produce applicable cell populations to gain maximal functional recovery. In the present study, human cord blood-derived iPSCs (hCBiPSCs) were differentiated into dopaminergic neurons utilizing two different in vitro protocols for neural induction: (protocol I) by fibroblast growth factor (FGF-2) signaling, (protocol II) by bone morphogenetic protein (BMP)/transforming growth factor (TGF-β) inhibition. After maturation, in vitro increased numbers of tyrosine hydroxylase (TH)-positive neurons (7.4% of total cells) were observed by protocol II compared to 3.5% in protocol I. Furthermore, 3 weeks after transplantation in hemiparkinsonian rats in vivo, a reduced number of undifferentiated proliferating cells was achieved with protocol II. In contrast, proliferation still occurred in protocol I-derived grafts, resulting in tumor-like growth in two out of four animals 3 weeks after transplantation. Protocol II, however, did not increase the number of TH + cells in the striatal grafts of hemiparkinsonian rats. In conclusion, BMP/TGF-β inhibition was more effective than FGF-2 signaling with regard to dopaminergic induction of hCBiPSCs in vitro and prevented graft overgrowth in vivo.